PEMBELAJARAN MATEMATIKA SD DENGAN MENGGUNAKAN MEDIA MANIPULATIF - Amir, Almira (FORUM PAEDAGOGIK, 2014)
AbstractLearning activity is an essential activity in all of the process education that engages two active agent, they are teacher and students. Teacher as an educator and instructor is one of the determinants for success in each effort education. Qualification of teacher in conveying material that can attractive enthusiasm and motivation of students for their learning is one of achievement that show level of teachers‟ professional itself.One of form of teacher management that can be done for increasing teachers‟ professional to achieve quality of learning is Lesson Study. Lesson study is “model of profession instruction of educator through learning as collaborative and continue rest on principles collegialities and mutual learning in community study. With lesson study, the teacher can ease to increase teaching quality and professionalism. Thereby, it can increase learning and produce the students has high quality.